2016
DOI: 10.18632/oncotarget.7603
|View full text |Cite
|
Sign up to set email alerts
|

PARP activation promotes nuclear AID accumulation in lymphoma cells

Abstract: Activation-induced cytidine deaminase (AID) initiates immunoglobulin diversification in germinal center B cells by targeted introduction of DNA damage. As aberrant nuclear AID action contributes to the generation of B cell lymphoma, the protein's activity is tightly regulated, e.g. by nuclear/cytoplasmic shuttling and nuclear degradation. In the present study, we asked whether DNA damage may affect regulation of the AID protein. We show that exogenous DNA damage that mainly activates base excision repair leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…AID localizes to the nucleus in response to DNA damage induced by ionizing radiation and other agents [ 28 , 41 , 42 ]. This raised the possibility that AID nuclear pulses are a response to damage caused by DNA deamination catalyzed by nuclear AID present at levels too low to detect by imaging.…”
Section: Resultsmentioning
confidence: 99%
“…AID localizes to the nucleus in response to DNA damage induced by ionizing radiation and other agents [ 28 , 41 , 42 ]. This raised the possibility that AID nuclear pulses are a response to damage caused by DNA deamination catalyzed by nuclear AID present at levels too low to detect by imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that activation of Parp1 by DNA damage results in reduced proteasomal degradation of AID, and increased nuclear accumulation [42]. YY1 does not regulate expression of Parp1, but our previous RNA transcript data in LPS plus IL4 activated splenic B cells show that YY1 positively regulates Parp2 expression [43].…”
Section: Discussionmentioning
confidence: 77%
“…As we previously found that PARP-1 regulates AID localization and stability upon exogenous DNA damage (20), we first asked whether the two enzymes interact in B cells undergoing SHM. Co-immunoprecipitation studies revealed that this is indeed the case: In the hypermutating and AID-expressing cell line Raji (34), immunoprecipitation with an AID antibody co-precipitated PARP-1, while this was not the case in non-mutating and AID low BJAB cells (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Our study was motivated by previous findings in our lab that implicated PARP-1 in the regulation of AID in case of exogenous introduction of DNA damage (20), which led to accumulation and stabilization of AID in the nucleus dependent on PARP-1 activity. Our present results shed more light on the mechanism of these previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation